Developing Teaching Material “Jurus Kilat! 6 Minggu Mahir Membaca Tanpa Eja” To Solve Initial Reading Difficulties in Primary School (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The purpose of this study is to determine the development, validity, effectiveness, and attractiveness of teaching material